Tetanus in Free-ranging Indian Grey Langur (Semnopithecus entellus) - Varun Kumar Sarkar; Pooja Solanki; Abhijit M Pawde; Ujjwal Kumar De; Shivansh Mehra (The Indian Veterinary Journal, 2024)
A two-year-old rescued male grey langur was arrived at referral veterinary polyclinic of institute with history of stiffness all over body. Clinical and physical examination showed elevated rectal temperature (104゜F), rigidity of limb, opisthotonus, locked jawand wound on tail tip. Based on the history and clinical findings the case was diagnosed as tetanus. The treatment initiated by administration of anti-tetanus serum, amoxicillin, and metronidazole, along with including dextrose normal saline and wound dressing with 6.5% hydrogen peroxide solution and povidone iodine ointment twice daily, unfortunately, langur died on fourth day of presentation.